Tuam Cathedral, fourteenth-century choir, south exterior wall, door, jamb and arch - O'Donovan, Danielle (My University, 2008)
South door of fourteenth-century choir of Tuam Cathedral. Perhaps a later insertion due to it's similarity to the fifteenth-century west door at Ross Errilly, which has a similar moulding and very similar hood stops. Moulding from intrados comprises: hollow chamfer, quadrant, hollow chamfer. The hood, from extrados to interior comprises: frontal fillet, hollow chamfer.
Keywords: quadrant; Architecture, Gothic -- Ireland; Galway (Ireland)--Buildings, structures, etc.; Gothic doorways; Late Medieval; moldings, hollow; roll moldings; hood moldings